2020
DOI: 10.1007/s11130-020-00801-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Carotenoids, Sensory Profiles and Volatile Compounds in Microwave-Dried Fruits of Three Different Loquat Cultivars (Eriobotrya japonica Lindl.)

Abstract: Evolution of carotenoids and volatile compounds in microwave-dried fruits of three different loquat cultivars (Eriobotrya japonica Lindl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…‘Virticchiara’ and ‘Claudia’ was found to be all- trans -βcarotene, while β-cryptoxanthin was predominant in dried loquat cv. Peluche [ 15 ]. As it is well-known that carotenoids are destroyed by heat treatment, a decrease of the amounts of total carotenoids is expected, as previous studies indicated a loss between 6% and 19% [ 26 ] and a loss between 24% and 42% [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…‘Virticchiara’ and ‘Claudia’ was found to be all- trans -βcarotene, while β-cryptoxanthin was predominant in dried loquat cv. Peluche [ 15 ]. As it is well-known that carotenoids are destroyed by heat treatment, a decrease of the amounts of total carotenoids is expected, as previous studies indicated a loss between 6% and 19% [ 26 ] and a loss between 24% and 42% [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Peluche [ 15 ]. As it is well-known that carotenoids are destroyed by heat treatment, a decrease of the amounts of total carotenoids is expected, as previous studies indicated a loss between 6% and 19% [ 26 ] and a loss between 24% and 42% [ 15 ]. Zeaxanthin (Zea) was the most stable carotenoid, with no significant differences among studied drying techniques, whilst it was observed by other authors that β-carotene was the most stable during the goji drying treatment [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of the sensory profiles of the mango fruits was performed using a descriptive method as previously reported [ 16 ]. The only difference from the method is the number of selected sensory attributes, which here is six.…”
Section: Methodsmentioning
confidence: 99%